Amoxicillin-Metronidazole vs Spiramycin-Metronidazole in the Treatment of Odontogenic Circumscribed Cellulitis: Randomized Clinical Trial in Odontostomatology (Global Journal of Medical Research, 2018)
Abstract not found
Keywords: cellulitis; amoxicillin; spiramycin; metronidazole; per-protocol; intent to treat